Duality of Donor–Acceptor Cyclopropane Reactivity as a Three‐Carbon Component in Five‐Membered Ring Construction: [3+2] Annulation Versus [3+2] Cycloaddition. Issue 21 (9th April 2013) - Volkova, Yulia A.; Budynina, Ekaterina M.; Kaplun, Alexey E.; Ivanova, Olga A.; Chagarovskiy, Alexey O.; Skvortsov, Dmitriy A.; Rybakov, Victor B.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
<x xml:space="preserve">Abstract</x> Quo vadis? The Lewis acid catalyzed reaction of (hetero)aryl‐derived donor–acceptor cyclopropanes with alkenes can be selectively directed along a [3+2] annulation pathway (see scheme). This new process provides convenient and efficient access to indanes and other cyclopentannulated (hetero)arenes, among which polyoxygenated 1‐arylindanes exhibit significant cytotoxicity against several cancer cell lines with an IC50 of 10−6–10−5 M.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>